PENGARUH DEWAN KOMISARIS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGUNGKAPAN RISIKO PERUSAHAAN - Revania, Reza; Aulia, Faisal; Julianti Efris Saputri, Eka; Amalia, Vera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of the board of commissioners and institutional ownership on corporate risk disclosure. The object of thisresearch is a banking sector company listed on the IDX in 2020-2024. By using the probability sampling method, the number of samples for this study was 12 companies with 5 years of observation. The independent variables are the board of commissioners, and institutional ownership. Meanwhile, the dependent variable used is corporate risk disclosure.This study uses a quantitative approach with data types in the form of secondary data. The testing of this study used multiple regression analysis techniques with SPSS analysis tools. The result sof the study show that the board of commissioners and institutional owner ship have a significant effect on the disclosure of corporate risks, which emphasizes the importance of internal and external supervision of parties within the company and optimal and appropriate corporate governance, so as to achieve the company's objectives optimally.